Kecanduan Bermain Game Online Smartphone Dengan Kualitas Tidur Siswa-Siswi di SMPK Hewerbura Watublapi Kabupaten Sikka - Pembronia Nona Fembi; Yosefina Nelista; Pasionista Vianitati (Jurnal Ilmiah Wahana Pendidikan, 2022)
Addiction to playing online games smartphone is a pleasure in playing because it can give a sense of its own satisfaction, so there is sense of repeating fun activities when playing smartphone online games. This could make someone be addiction and can reduce sleeping quality. Addiction to playing online smartphone games is a pleasure in playing because it can give a sense of its own satisfaction, so there of this study was to determine the relationship between addiction to playing smartphone online games with the quality of student at SMPK Hewerbura Watublapi, Sikka Regency. The type of research used in this research was correlation analytic research with a cross-sectional approach, the population in this study was students of class VIII in SMPK Hewerbura Watublapi, Sikka Regency with the sample in this study amounted to 80 people, the sampling technique used total sampling. The statistical test was the Spearman correlation test, the data were collected through questionnaires. The results of the study showed that of the 80 respondents who were addicted to online smartphone games with poor sleep quality category as many as 41 people and addiction to playing heavy smartphone online games with poor sleep quality category as many as 30 people. The results of the Spearman correlation test obtained p value (0.013) < α (0.05) with a correlation coefficient of 0.276 in the direction of the positive relationship. It means that H0 was rejected and Ha was accepted, this means that there was a significant relationship between addiction to playing smartphone online games and the sleep quality of students at SMPK Hewerbura Watublapi, Sikka Regency, which has a weak relationship where the higher level of addiction to playing smartphone online games affects the students sleep quality.The results of this study can be concluded that more students experience poor sleep quality because students do not know the negative impact of playing online games for a long time. Based on this result, it is expected that parents should control their children in playing online games and school must provide information regarding the negative impacts of online games.